"I'm not being serviced; I'm being cared for": A mixed methods study of patients' and nurses' perceptions of community oncology nursing delivered by a Community Intervention Team. (October 2022) - O'Connor Power, Fiona; Beatty, Siobhan; Dunne, Neil; O'Connell, Liz; O' Riordan, Norma; Sloane, Heather; Prizeman, Geraldine; O'Sullivan, Karin; Butler, Éadaoin; Howlin, Claire; Byrne, Gobnait
Abstract: Purpose: Many patients do not have access to community oncology nursing care in a primary setting and are completely reliant on tertiary hospital care. The aim of this study is to gain an understanding of oncology patients' and nurses' perceptions of community oncology nursing, delivered by an urban Community Intervention Team (CIT) in Ireland. Methods: A descriptive, concurrent mixed methods approach was used which included semi-structured interviews with 14 oncology patients and an online survey of 27 hospital and community nurses. Thematic analysis and descriptive statistics were used to analyse the data. Results: Six broad themes captured patients' views. Right care related to patients' satisfaction with the range of care available. Right place reflected positive views of the physical setting and the option for homecare for those that needed it. Right time represented patients' comments about the increased appointment efficiency, flexibility, and availability of the service out-of-hours, compared to hospital-based care. Right people was based on patients' portrayals of community cancer nurses as professional, confident, friendly, reassuring and relatable. Integration and communication reflected the communication between the services and patients' impressions of how the services were integrated together. The last theme was improvements to the CIT service. Hospital nurses reported satisfaction with the CIT service while CIT nurses responses suggest the need for better communication with hospital partners. Conclusion: Patients had positive perceptions of the service provided by the CIT. Both hospital and community cancer nurses were satisfied with the service and reported that they would like to see an expansion of community oncology nursing services delivered by the CIT. Highlights: Main focus on the patient's perspective about community oncology nursing. The community oncology nursing service enhanced patients' quality of life. Insight into patients' views of integrated care during oncology treatment.